2019
DOI: 10.1021/acs.orglett.9b04459
|View full text |Cite
|
Sign up to set email alerts
|

Iron Hydride Radical Reductive Alkylation of Unactivated Alkenes

Abstract: Iron-catalyzed hydrogen atom transfer-mediated intermolecular C-C coupling reactions between alkenes and tosylhydrazones, followed by in situ cleavage of the tosylhydrazine intermediates using Et3N, are described. The process involves a new strategic bond disconnection resulting in the reductive alkylation of non-activated alkenes. The reaction is operationally simple, proceeds under mild conditions, and has a wide substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
1
25
0
4
Order By: Relevance
“…Subsequently, N ‐cyanamide alkenes have been developed as radicophiles for 1,3‐dicarbonyl, trifluoromethyl, phosphoryl, and sulfonyl radicals . Since its discovery in the early 1960s, metal‐hydride hydrogen atom transfer (HAT) has become a widely established method for the generation of carbon‐centred radicals from alkenes and a variety of radicophiles have proven compatible . As an extension of our previous methodology, which utilised HAT to mediate cyclisation between alkenes and nitriles, we looked to develop this further by utilising N ‐cyanamide alkenes to access complex (spiro)quinazolinone scaffolds (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, N ‐cyanamide alkenes have been developed as radicophiles for 1,3‐dicarbonyl, trifluoromethyl, phosphoryl, and sulfonyl radicals . Since its discovery in the early 1960s, metal‐hydride hydrogen atom transfer (HAT) has become a widely established method for the generation of carbon‐centred radicals from alkenes and a variety of radicophiles have proven compatible . As an extension of our previous methodology, which utilised HAT to mediate cyclisation between alkenes and nitriles, we looked to develop this further by utilising N ‐cyanamide alkenes to access complex (spiro)quinazolinone scaffolds (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
“…[10] Since its discovery in the early 1960s, [11] metal-hydride hydrogen atom transfer (HAT) has become aw idely established methodf or the generation of carbon-centred radicals from alkenes [12] and av ariety of radicophiles have provenc ompatible. [13][14][15][16][17][18][19][20][21][22] As an extension of our previousm ethodology,w hich utilised HATt om ediate cyclisation between alkenes and nitriles, [17] we looked to developt his furtherb yu tilising N-cyanamide alkenest oa ccess complex (spiro)quinazolinone scaffolds (Scheme 2b). It has been shown that the introduction of sp 3 centres, such as the spirocentre of spirocycles, can greatlye nhance am olecule's potential to be a drug candidate.…”
mentioning
confidence: 99%
“…More recently, the Bradshaw group has been exploring the potential use of tosyl hydrazones in reductive couplings with olefins initiated via metal hydride atom transfer [ 96 97 ]. In 2020, they realized that formal hydroalkylated products could be obtained by coupling substituted tosyl hydrazones with olefins ( Scheme 29 ) [ 98 ], similarly to the hydromethylation protocol developed by Baran [ 95 ] ( Scheme 28 ). The higher stability of the substituted hydrazones obviated their generation in situ , and as ethanol was identified as a better solvent in the initial coupling step, no solvent exchange was necessary in the fragmentation step of the hydrazide intermediate.…”
Section: Reviewmentioning
confidence: 99%
“… The hydroalkylation of unactivated olefins via iron-mediated reductive coupling with hydrazones (Bradshaw (2020) [ 98 ]). …”
Section: Reviewmentioning
confidence: 99%
“…This methodology has further evolved into intermolecular examples of alkene/tosylhydrazone Csp 3 -Csp 3 coupling. 121…”
Section: Short Review Syn Thesismentioning
confidence: 99%